The Role of Parents in the Implementation of Inclusive Education at MI Ma'arif 56 Tempurejo, Jember, East Java - Kurnia , Nury; Syamsiyah, ST Fanatus (Program Studi Pendidikan Luar Biasa Universitas PGRI Argopuro Jember, 2024)
This research investigates the role of parents in inclusive education at MI Ma'arif 56 Tempurejo, Jember, East Java. Using questionnaire and interview methods, data was collected to evaluate the level of parental involvement in supporting inclusive education and identify the obstacles faced. The results showed that the majority of parents showed positive involvement, although some had difficulty understanding the concept of inclusion. The discussion emphasized the need to strengthen parental involvement and address barriers, such as lack of understanding of inclusion and lack of support from schools. The implications of these outcomes can be used to improve the inclusive education program at MI Ma'arif 56 Tempurejo so that it is more inclusive and effective for all students. Thus, this research makes an important contribution in understanding the role of parents in inclusive education in Indonesia.